DIMENSI TAUHID DALAM PEMBELAJARAN ILMU PENGETAHUAN ALAM BERBASIS FILSAFAT NATURALISME AUGUST COMTE - Fajarwati, Lusy; Irawan; Hasanah, Aan (Academic Journal of Islamic Principles and Philosophy, 2023)
This article raises the problem of the lack of integration of tauhidic values ​​in Natural Sciences (Ilmu Pengetahuan Alam) learning in connection with the non-inclusion of tauhidic values ​​in the Learning Implementation Plan (Rencana Pelaksanaan Pembelajaran). This research aims to reveal how aspects of tauhid can be integrated in the context of Natural Sciences (IPA) learning, as well as how the concept of Naturalism proposed by August Comte can be applied in natural sciences learning. So the results can provide guidance to educators and teachers about the importance of the tauhid dimension in science education and inspire discussions about how Comte's naturalism can be applied meaningfully in modern and diverse educational contexts. The method used is philosophical qualitative, with an emphasis on conceptual analysis and Comte's philosophical understanding of Naturalism. The results of this research will highlight the challenges faced by teachers in integrating monotheistic values ​​in science learning, as well as the impact of this lack of integration on the education and development of students. Through a philosophical qualitative approach, it will also show an understanding of how teachers can understand and apply tauhid dimension in science learning effectively. Thus, the findings in it will provide insight into how to increase the integration of tauhidic values ​​in integrated natural science education, by referring to August Comte's naturalist concepts.